A PENERAPAN ETIKA BISNIS DAN TANGGUNG JAWAB PEMBERI KERJA DAN HAK KARYAWAN TERHADAP KINERJA KARYAWAN (Study Kasus Pada Customer Service Di PT Bank Rakyat Indonesia (Persero),.Tbk): PENERAPAN ETIKA BISNIS DAN TANGGUNG JAWAB PEMBERI KERJA DAN HAK KARYAWAN TERHADAP KINERJA KARYAWAN (Study Kasus Pada Customer Service Di PT Bank Rakyat Indonesia (Persero),.Tbk) - Rita Sri Silvia Pamuji; Yanneri Elfa Kiswara (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
In its implementation, the principles of business ethics in an organization and customer service are very related, such as when provudung services to customers, ethics must be used. Tjis is intended to create a good relationship between customers at PT Bank Rakyat Indonesia. In principle, business atehics is everything about guiding norms for a company in making decision, with the intention that good relation between the company and stakeholders are maintained, of course must use the rules that have been in effect. PT Bank Rakyat Indonesia has been good in carrying out its duties so that customers feel satisfied and fulfilled with the wishes expected by customers, both from service and banking ethics. Problems that occur at this time are deviations in terms of providing excellent service, namely there are multiple positions or commonly referred to as overlapping work in a work unit, for example customer service provider not only serves customers who come to convey various kind of complaints, but also does some work, and the work that shuold be done by the back office such as administering credit completeness and credit contract. So that more or less will reduce the excellent service that a customer service should do with a small example, ignoring basic service concept such as smiles, greetings wich are often referred to 3S. The method used in writing journals about the application of business ethic and employer responsibilities and employee rights to employee performance is a descriptive research method, because this study aims to only describe the facts as they are and describe the fact on the object under study. Irredularities commited by PT Bank Rakyat Indonesia (Persero),.Tbk, which are contary to the principles of business ethics in this company, namely in terms of providing excellent service, there are multiple positions or commonly referred to as overlapping work in unit. PT Bank Rakyat Indonesia (Persero),.Tbk need to be reviewed again regarding the duties and function of each position. It’s just that there are very few deviations that occur because this in a work unit in this company there is an overlapping position.